Penggunaan Kain dari Bahan Sutra Campuran dan Sintesis dalam Tinjauan Fikih Islam: The Use of Fabric Made from Mixed Silk and Synthetic Materials for Men: An Islamic Jurisprudence Perspective - Mukran H. Usman; Sirajuddin, Sirajuddin; Nur Faiz (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to investigate and understand the rulings on the use of mixed and synthetic silk fabrics for men from the perspective of Islamic jurisprudence. The methodology employed in this research is library research, collecting data from the Qur’an, Hadiths, Islamic jurisprudence texts, books, scholarly journals, encyclopedias, and electronic sources. A normative approach is used to examine the Qur’anic evidence, Hadiths, and the opinions of scholars concerning the use of silk fabric. The findings of the study are as follows. First, the use of silk fabric by men is a matter of debate among Islamic jurists. Second, in general, the use of natural silk fabric is prohibited for men based on the Hadiths of the Prophet Muhammad (peace be upon him). Third, artificial or mixed silk fabrics made from synthetic materials or plant fibers are permissible because the basic ruling on clothing in Islam is that it is permissible. The implications of this study are expected to serve as a reference, literature, or consideration for the academic world, as well as a source of positive guidance and information for the government, entrepreneurs, and the general public.